Vertical differentiation for gifted, advanced, and high-potential students 25 strategies to stretch student thinking - Mofield, Emily 1979- (New York, NY Routledge, Taylor & Francis Group, 2023)
"Vertical Differentiation for Gifted, Advanced, and High-Potential Students outlines 25 engaging tools and strategies to stretch student thinking, promote deep learning, and provide layers of challenge in the classroom and beyond. Each strategy is expertly designed to foster deep inquiry and conceptual understanding by guiding students to justify conclusions, apply critical and creative thinking, develop solutions to real-world problems, and transfer learning across contexts. Packed with both "tried and true" thinking models and new, innovative ideas with concrete examples, this resource ensures that no matter where students are in their learning journey, they'll find themselves challenged and engaged. This book is essential reading for educators looking to support and extend student thinking across content areas and grade levels"--
Includes bibliographical references.
Keywords: Individualized instruction; Special education; Critical thinking -- Study and teaching; Gifted children -- Education